Optimalisasi Layanan Nazhir Berbasis Digital pada Perwakilan Badan Wakaf Indonesia (BWI) Kabupaten Bantul - Priyadi, Unggul; Achiria, Siti; Adli, Akmal Inan Hafidh (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service aims to increase the role of BWI and Nazhir representatives in efforts to make waqf land assets productive by building a digital-based waqf land asset information service system for BWI representatives in Bantul Regency. The method of implementing this service uses training and counseling with a participatory approach which includes needs analysis and Focus Group Discussion, development, implementation, evaluation, and follow-up based on predetermined success indicators. The result of this community service activity is the formation of a website-based Nazhir service information system for BWI and Nazhir representatives in Bantul Regency, which can help and provide convenience to BWI and Nazhir representatives in monitoring the development and process of mapping waqf land assets and provide convenience for prospective waqf partners to establish cooperation to produce waqf land assets.